Development of foreign trade relations between Ukraine and Turkmenistan - Penchuk, Anna; Tur, Olesya (My University, 2020)
The article analyzes the development of foreign trade relations between Ukraine and Turkmenistan. The aim of the article is to study the trends and state of the development of foreign trade relations between Ukraine and Turkmenistan, identifying problems and promising directions for their overcoming. The methodology of the study is the foreign and Ukrainian scientific literature, analysis of statistical data (over the last ten years), which have shown the results of foreign trade relations between the countries. The perspective directions for deepening of foreign trade relations between Ukraine and Turkmenistan should be a sale of Ukrainian pipes, gas-pumping units, equipment for replacing insulating coatings at gas pipelines, implementation of programs for major repair and reconstruction of Turkmenistan’s gas transportation system and cooperation of «Naftogaz of Ukraine» with the state-owned concern «Turkmennaft». The main provisions and conclusions of the article can be used for the preparation of analytical materials and practical recommendations for government agencies, as well as individual enterprises – participants of foreign trade relations. У статті аналізується розвиток зовнішньоторговельних відносин між Україною та Туркменістаном. Метою статті є дослідження тенденцій та стану розвитку зовнішньоторговельних відносин між Україною та Туркменістаном, визначення проблем та перспективних напрямів їх подолання. Методологією дослідження є зарубіжна та українська наукова література, аналіз статистичних даних (за останні десять років), які показали результати зовнішньоторговельних відносин між країнами. Перспективними напрямками поглиблення зовнішньоторговельних відносин між Україною та Туркменістаном мають стати продаж українських труб, газоперекачувальних агрегатів, обладнання для заміни ізоляційних покриттів на газопроводах, реалізація програм капітального ремонту та реконструкції газотранспортної системи Туркменістану та співробітництво НАК «Нафтогаз України» з державним концерном «Туркменнафта». Основні положення та висновки статті можуть бути використані для підготовки аналітичних матеріалів та практичних рекомендацій для державних органів, а також окремих підприємств – учасників зовнішньоекономічних відносин.
Keywords: services; foreign trade relations; foreign trade turnover; export; import; goods; зовнішньоторговельні відносини; зовнішньоторговельний оборот; експорт; імпорт; товари; послуги; кафедра економіки праці та менеджменту